2013
DOI: 10.1038/ejhg.2013.238
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the residual CFTR gene expression in human nasal epithelium cells bearing CFTR splicing mutations causing cystic fibrosis

Abstract: The major purpose of the present study was to quantify correctly spliced CFTR transcripts in human nasal epithelial cells from cystic fibrosis (CF) patients carrying the splicing mutations c.580-1G4T (712-1G4T) and c.2657 þ 5G4A (2789 þ 5G4A) and to assess the applicability of this model in CFTR therapeutic approaches. We performed the relative quantification of CFTR mRNA by reverse transcription quantitative PCR (RT-qPCR) of these splicing mutations in four groups (wild type, CF-F508del controls, CF patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Primary respiratory cell cultures derived from CF patients are considered the gold standard to validate compound efficacy 27,62 and might help as an ex vivo test to predict the propensity of each individual patient to benefit from the in vivo administration of the candidate drug. We observed that cysteamine could rescue >70% of the expression of functional CFTR mutant in ex vivo cultures of freshly isolated patients' nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Primary respiratory cell cultures derived from CF patients are considered the gold standard to validate compound efficacy 27,62 and might help as an ex vivo test to predict the propensity of each individual patient to benefit from the in vivo administration of the candidate drug. We observed that cysteamine could rescue >70% of the expression of functional CFTR mutant in ex vivo cultures of freshly isolated patients' nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The CFTR minigenes were produced using a “sticky feet PCR” strategy to insert CFTR introns (IVS) IVS14, IVS15, and IVS16 consecutively into the pCDNA5/FRT/CFTR mammalian expression vector carrying the complete wt‐CFTR cDNA as described previously [Masvidal et al., ]. Thus, “triple minigenes” consist of the full‐length 4.5 kb CFTR cDNA plus relevant intronic regions (IVS14, IVS15, and IVS16), from herein referred as wt and 2657+5G>A mutant (Mut) CFTR splicing minigenes.…”
Section: Methodsmentioning
confidence: 99%
“…CFTR protein detection was performed by Western blot as previously [Masvidal et al., ]. Briefly, proteins were separated by SDS‐PAGE 7% (w/v) gel and CFTR was detected using the anti‐CFTR monoclonal antibody M3A7 (1:2,000 dilution) (EMD Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations